Chetty: the unforgotten - Haminuddin, Norsuhana; Abdullah, Nik Norasyira; Norazman, Nadhirah Husna; Azli, Aina Farahin; Fadzil, Nur Sakinah; Wan Shazli, Wan Nuriffa Azima; Mohd Fadzil, Nur Hidayah; Abd Rahman, Nur Hidayah (Research Management Unit (RMU), Universiti Teknologi MARA Cawangan Pulau Pinang, 2019)
Melaka is one of the historical cities which is famous with its culture and heritage values. Unfortunately, Chetty’s community is closely to be left out and forgotten despite of any tourism commercialization by the Melaka State Government. Therefore, in order to make this Chetty’s community to be acknowledged by the local people and tourists around the world, the concept of Augmented Reality is vital to be introduced in order to curb the distinction of this community. This initiative is produced in live brochure form to promote the culture and custom of the Chetty’s community in Melaka which resulted from an improper medium of marketing and promotion. Furthermore, this live brochure comprises of all the information related to the Chetty’s community such as navigation, attractions, activities, customs and lifestyle that present the Chetty’s features which located in Kampung Gajah Berang. Nevertheless, this initiative can lift up their image as one of the unique minority ethnics in Melaka World Heritage Site. The live brochure will also benefit the Chetty’s community in tourism activities specifically in preserving the priceless values of that community based on their history and custom which could be protected. Consequently, it will become one of the attractive tourism destinations in Melaka World Heritage Site with exclusive design of the brochure and able to captivate the tourists’ attention.